(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2024)
This article explores theoretical possibilities for the study of educational policies, advocating for the adoption of the policy cycle approach, which encompasses the contexts of influence, text production, and practice. Additionally, the theory of enactment is proposed to deepen understanding of how policies are implemented in practice. Methodologically, the use of principles from narrative and (auto)biographical research is recommended, which emphasise subjective thoughts, perceptions, and meanings. These research approaches foreground the experiences, inspirations, emotions, and meanings of those involved, prioritising the primacy of their lived experiences. It is argued that centralising the understanding of policies in an individual and collective level enables a clearer grasp of practices that bring to life the meanings of formulated and implemented educational policies. The article is initially structured by presenting and clarifying the proposed theoretical frameworks, followed by a discussion of potential intersections, aiming to understand how public policies impact and are shaped by the human condition. Keywords: Policy cycle approach. Theory of enactment. (Auto)biographical research.